THE ETHICAL VALUES EMPOWERMENT AS EXPOUNDED IN CHANKAM PERIOD WITH SPECIAL REFERENCE OF THE LETURER NALADYAR - Kanesarajah, K. (International Journal of Psychosocial Rehabilitation, 2020)
The Tamilian Philosophy is an important part of the South Eastern Philosophy. It is analysis man, nature, metaphysics, etc. In the western scholars are divided in western thoughts in many way. Although the South eastern scholars are divided many periods. The Chamkam period is most important period in the history of Tamil literature. It is said that during this period there are eighteen text are more influence in the Philosophical thoughts. As far as literature Naladyar is concerned which proses four phrases describes what moral values to be followed by human beings and what should not perform morality human being. Sense the modern world seems to be ignoring the moral values it is now high time to pay a second visit to the moral values stipulated in liteeneatuees in these respect this particular study based on the qualitative research of the said literature on the interpretation made me of it and then the studies many journals and articles.